Contemporary Religious Life in Russia's Provinces: A New Source - Daniel, Wallace L. (The journal of ecclesiastical history, 2017)
In 1976, shortly after leaving the Soviet Union with his wife and daughter, the Leningrad native and Dostoevsky scholar Evgenii Aleksandrovich Vagin reflected on Russia's past and its possible future. He emphasised the central role that he believed the provinces would play. Unquestionably', he said, the future of Russia depends a great deal on the extent to which the provinces will awaken, the extent to which all the processes of democratisation and spiritual rebirth will touch their depths.'